Exploring The Fundamental Aspect of Grassroot Football Academy: A Case Study in Indonesia [Explorando el aspecto fundamental de la academia de ftbol base: un caso de estudio en Indonesia] - Zulakbal Abd Karim, Jaffry Zakaria (Tanjung Malim, 2024)
Exploring The Fundamental Aspect of Grassroot Football Academy: A Case Study in Indonesia [Explorando el aspecto fundamental de la academia de ftbol base: un caso de estudio en Indonesia] by Zulakbal Abd Karim, Jaffry Zakaria